Thinking about it: a note on attention and well-being losses from unemployment - Dolan, Paul. (2013)
This article investigates Schkade and Kahneman's (1998) maxim that ‘Nothing in life is quite as important as you think it is while you are thinking about it.’ This article shows that whilst becoming unemployed hurts psychologically, unemployment has a greater impact on happiness if the person also regards it as an important event that took place in the last year. This finding, particularly if it is replicated for other domains, such as health and income, will have important implications for how we think about the impact of objective circumstances on well-being and about well-being more generally.